Spotaneous intracranial haemorrhage in paediatric oncology patients - Lieberman, L; Betcherman, L; Pole, J; Estcourt, L; Sung, L; Stanworth, S (Wiley, 2016)
Intracranial haemorrhage (ICH) is a rare but serious complication in pediatric oncology patients. ICH risk factors differ between the general population and those with cancer. In adults, several factors have been shown to increase the risk of ICH, including sepsis. Few studies have examined these risk factors in the pediatric oncology population.